2016
DOI: 10.1093/qje/qjw004
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Inequality in the United States since 1913: Evidence from Capitalized Income Tax Data *

Abstract: This paper combines income tax returns with macroeconomic household balance sheets to estimate the distribution of wealth in the United States since 1913. We estimate wealth by capitalizing the incomes reported by individual taxpayers, accounting for assets that do not generate taxable income. We successfully test our capitalization method in three micro datasets where we can observe both income and wealth: the Survey of Consumer Finance, linked estate and income tax returns, and foundations’ tax records. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

72
1,112
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,208 publications
(1,196 citation statements)
references
References 39 publications
72
1,112
3
9
Order By: Relevance
“…The increase in wealth concentration is due to the surge of top incomes combined with an increase in saving rate inequality. Top wealth-holders are younger today than in the 1960s and earn a higher fraction of total labor income in the economy.‖ (Saez, Zucman 2016).…”
Section: Ethno-nationalism Triggered By Economic Grievancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in wealth concentration is due to the surge of top incomes combined with an increase in saving rate inequality. Top wealth-holders are younger today than in the 1960s and earn a higher fraction of total labor income in the economy.‖ (Saez, Zucman 2016).…”
Section: Ethno-nationalism Triggered By Economic Grievancesmentioning
confidence: 99%
“…Pension wealth has continued to increase, but not enough to compensate for a surge in mortgage, consumer credit, and student debt. The key driver of the declining bottom 90% share is the fall of middle-class saving, which may partly owe to the low income growth, to financial deregulation leading to some forms of predatory lending, or to growing behavioral biases in the saving decisions of middle-class households (Saez, Zucman 2016).…”
mentioning
confidence: 99%
“…Before 1913 the change in inequality was given as a weighted geometric average of the change in EF and the change in the top 1% fraction of wealth (Williamson and Lindert 1980), with a weighting of 3 applied to EF. After 1913 the change in inequality was the geometric average of the change in EF, top 1% income share (Piketty and Saez 2007) and top 0.1% wealth share (Saez and Zucman 2016), with a weighting of 4 for EF. The index was smoothed with an exponential average (α = 0.2).…”
Section: Mechanism For Generating Rising Inequalitymentioning
confidence: 99%
“…Research over this time has shown that inequality underwent a dramatic decline from high levels before 1930 to a nadir around 1980, from which it has returned to its level in the twenties, suggesting that inequality may be cyclical (Piketty and Saez 2007;Saez and Zucman 2016). If so, a trend change to falling inequality could happen again, the prospect of which is intriguing politically as well as academically.…”
Section: Introductionmentioning
confidence: 98%
“…However, reports have been made that the Great Recession exacerbated the uneven wealth distribution in the United States (e.g., Kochhar and Cilluffo 2017;Wolff 2014), and, at the same time, wealth inequality has been addressed as an increasing social problem by both organizations and scholars (e.g., Congressional Budget Office 2016; Organization for Economic Cooperation and Development 2016; Saez and Zucman 2016). Concerns about wealth inequality is not a phenomenon restricted to the United States as can be seen from the frenzied worldwide reaction to the publication of Capital in the Twenty-First Century by Piketty (2014).…”
Section: Introductionmentioning
confidence: 99%